The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4269/ajtmh.2011.10-0609
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability and Dengue Fever in Warm and Humid Mexico

Abstract: Multiple linear regression models were fitted to look for associations between changes in the incidence rate of dengue fever and climate variability in the warm and humid region of Mexico. Data were collected for 12 Mexican provinces over a 23-year period (January 1985 to December 2007). Our results show that the incidence rate or risk of infection is higher during El Niño events and in the warm and wet season. We provide evidence to show that dengue fever incidence was positively associated with the strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
82
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 31 publications
6
82
0
4
Order By: Relevance
“…Additionally, ONI remains the most important climate variable when Tmin and precipitation are included in the models, indicating that the influence of ENSO on dengue extends beyond these variables, which was found in a previous study in Mexico. 17 We found that ENSO has a strong influence on anomalies in Tmin, which was indicated by a positive association during both time periods (1995-2010 and 2001-2010) (Figure 3). Anomalies in Tmax and Tmean were also positively associated with ENSO, although the association was weaker.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Additionally, ONI remains the most important climate variable when Tmin and precipitation are included in the models, indicating that the influence of ENSO on dengue extends beyond these variables, which was found in a previous study in Mexico. 17 We found that ENSO has a strong influence on anomalies in Tmin, which was indicated by a positive association during both time periods (1995-2010 and 2001-2010) (Figure 3). Anomalies in Tmax and Tmean were also positively associated with ENSO, although the association was weaker.…”
Section: Discussionmentioning
confidence: 81%
“…17,[46][47][48] Likewise, field studies in this region found that Tmin and precipitation were the most important local climate predictors of seasonal Ae. aegypti population dynamics (StewartIbarra AM and others, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this investigation, we selected two pathogens: influenza and dengue. The rationale for selecting these diseases is that they both have strong seasonality-which can drive accelerating spread in some models 6,7 -and have rich historical data sets. However, because dengue is a vectored pathogen, and influenza is not, we expect the importance of relational exchange to be far greater for influenza 8,9,10 .…”
mentioning
confidence: 99%
“…2 Climate influences dengue transmission through impacts on the vector (e.g., growth and development, availability of habitat, survivorship) 3 and impacts on the virus (e.g., length of extrinsic incubation period, [EIP]). 4,5 Correlations have been found between weather and climate variability and dengue incidence, including distinct seasonal variability, 6 El Niñ o Southern Oscillation index variability, [7][8][9][10][11] and monthly [12][13][14] and weekly 15 weather variability. The potential impact of climate change on dengue has been extensively explored and estimated via scenario-based modeling, with prediction of expansion in the geographic distribution of dengue under climate change scenarios.…”
Section: Introductionmentioning
confidence: 99%